1983
DOI: 10.1002/j.1552-4604.1983.tb02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Pharmacokinetics of Theophylline in Peritoneal Dialysis and Hemodialysis

Abstract: Dialysis clearance and drug recovery of theophylline were investigated in three peritoneal dialysis patients and the results were compared with those obtained from five hemodialysis patients. Peritoneal clearance averaged 9.5 ml/min, in contrast with the hemodialysis clearance of 84.8 ml/min, indicating a relative inefficiency of peritoneal dialysis with regard to theophylline removal. Theophylline half-life was reduced substantially during hemodialysis, 2.0 to 3.2 hours, in comparison with the normal half-lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Lee et al 73 reported similar values (9.5 ml/minute). Thus, peritoneal dialysis is much less effective than haemodialysis which can achieve clearances of 112 ml/minute74 in adults, if blood flow is maintained.…”
Section: Rationalementioning
confidence: 61%
“…Lee et al 73 reported similar values (9.5 ml/minute). Thus, peritoneal dialysis is much less effective than haemodialysis which can achieve clearances of 112 ml/minute74 in adults, if blood flow is maintained.…”
Section: Rationalementioning
confidence: 61%
“…The use of peritoneal dialysis (PD) is infrequent in poisoning, due to its limited clearance capacity . The overall clearances are much lower with PD than other techniques.…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…The overall clearances are much lower with PD than other techniques. For example, clearances for theophylline are 10 ml/minute with PD compared to 85 ml/minute with IHD .…”
Section: Peritoneal Dialysismentioning
confidence: 99%
“…Peritoneal dialysis (PD) also uses the principle of passive diffusion, although fluid and solute exchange occurs in the peritoneal cavity across the peritoneal membrane. The use of PD in poisoning has almost disappeared due to its limited clearance capacity compared with IHD . In PD, increasing the dialysate flow rate ( Q D ) maximizes clearance.…”
Section: Principles Of Poison Removalmentioning
confidence: 99%